(untitled) (Scientific journal of the Fergana State University, 2023)
FT-IR spectrometers are used to solve various problems of modern analytics. Designed for qualitative analysis, checking the refractive index of thin films, the thickness of thin films. We studied the mid-infrared transmission and absorption spectra, refractive index, layer thickness, standard deviation, incident angle, average interference fringes, and the coupling between silicon and oxygen of thin films obtained by the ion-plasma method.